2002
DOI: 10.1021/jp013155h
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Behavior of Protoporphyrin IX in Aqueous Solutions:  Clear Evidence of Vesicle Formation

Abstract: The aggregation behavior of protoporphyrin IX in aqueous solution, as a function of pH and ionic strength, has been studied by means of UV/vis, fluorescence emission spectroscopy, and resonant light scattering (RLS) techniques. Our experimental results agree with previous literature assignments: (i) protoporphyrin IX is a monomer in the pH range 0-3, (ii) a dimer is present for pH > 8, and (iii) higher aggregates are present in the pH range 3-7. Addition of sodium chloride up to 0.3 M to a porphyrin solution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(163 citation statements)
references
References 35 publications
9
150
2
2
Order By: Relevance
“…According to Scolaro et al (2002), porphyrins exhibit aggregation, a π-π stacking interaction in water while spectroscopic studies performed in water as a function of pH demonstrated that they are monomer between pH 0-3; dimmer in pH above 8 and higher aggregates in the pH 3-7. At pH 1, PpIX absorption spectra exhibits a strong absorption band (B-band) at λ (nm) = 406 (1.7) and four weaker absorption bands (Q-bands) at λ (nm) = 516 (9.6); 554 (17.2); 600 (11.6) and 626 (8.0).…”
Section: Resultsmentioning
confidence: 99%
“…According to Scolaro et al (2002), porphyrins exhibit aggregation, a π-π stacking interaction in water while spectroscopic studies performed in water as a function of pH demonstrated that they are monomer between pH 0-3; dimmer in pH above 8 and higher aggregates in the pH 3-7. At pH 1, PpIX absorption spectra exhibits a strong absorption band (B-band) at λ (nm) = 406 (1.7) and four weaker absorption bands (Q-bands) at λ (nm) = 516 (9.6); 554 (17.2); 600 (11.6) and 626 (8.0).…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, the fluorescence intensity of free PPIX increased nonlinearly with a rising concentration of PPIX. This may be caused by its low solubility and self-aggregation (37)(38) and may affect the PPIX concentration determination based on fluorescence spectroscopy. The EfeB-PPIX complex has a much higher fluorescence intensity compared with that of free PPIX at a corresponding concentration.…”
Section: Efeb Binds Ppix and Enhances Its Fluorescence Intensity-mentioning
confidence: 99%
“…The EfeB-PPIX complex can also be purified from cell lysate containing EfeB and additive PPIX. However, the ITC run for PPIX and EfeB does not provide a significant result because of its low solubility and self-stacking (37)(38). Titrating heme into the EfeB-PPIX complex gives a K d of 2.14 (Ϯ0.5) ϫ 10 Ϫ7 M (supplemental Fig.…”
Section: Efeb Binds Ppix and Enhances Its Fluorescence Intensity-mentioning
confidence: 99%
“…The LED downlight was chosen because PpIX exhibits maximum absorbance at 409 nm light but also absorbs components at longer wavelengths in the visible light range [21], and white light contains all visible light, ranging from 400-700 nm. Furthermore, when considering the LED downlight properties and size, the heat generated by the light is very low and it is useful for the exposure of an entire 96-well plate.…”
Section: In Vitro Pdt Studymentioning
confidence: 99%
“…PpIX exists as a monomer in the pH range 0-3, as an aggregate in the pH range 3-8 and as a dimer in any pH greater than 8 [21]. Aggregation behavior of PpIX in neutral water makes it inappropriate for use in physiological studies.…”
Section: Introductionmentioning
confidence: 99%